The Effect of Company Size, Exchange Rate and Earnings Per Share on Stock Returns - Elfiswandi Elfiswandi; Cindy Angela; Muhammad Fikri Ramadhan (UPI YPTK Journal of Business and Economics, 2022)
This study aims to examine and analyze the effect of firm size, exchange rate, earnings per share and capital structure as control variables on stock returns. All manufacturing companies listed on the Indonesia Stock Exchange for the period 2013 – 2017 are the population in this study. By using purposive sampling method, 100 companies were selected as samples in the study. The method of collecting data is library research and secondary data from the official publications of the Indonesia Stock Exchange and the official website of Bank Indonesia. Panel and regression methods are used as an analytical tool in this study. The results obtained in the study are, stock returns are significantly affected by firm size, exchange rates and earnings per share either partially or simultaneously. Meanwhile, when using capital structure as a control variable on stock returns, the results show that the variables of firm size, exchange rate and earnings per share are partially stated to have no significant effect.